Assessment of Prevalence of the Most Common Cancers at a Tertiary Care Hospital in Al Ahsa, Kingdom of Saudi Arabia (Medical Forum Monthly, 2024)
Objective: To assess the prevalence of most common cancers.Study Design: Observational / analytic study.Place and Duration of Study: This study was conducted at King Fahd Hospital (KFH), Al Ahsa, Kingdom of Saudi Arabia (KSA) from January 2015 to December 2015.Materials and Methods: This study was conducted among 200 cancer patients, visited KFH, Al Ahsa. Total 200 patients were included in the study. Adult patients of age 15 to 85 years were included. The data was analyzed using SPSS 16. Results: Among total 200 cancer patients, males accounted for 108 (54%) and females for 92 (46%). Age of the male patients at presentation was 45 to 85 (mean 65) years and age of the female patients was 49 to 83 (mean 66) years. Only 2 cases of Osteosarcoma were found in young age males (21 to 23 years), and only 2 cases of breast cancer were found in young age females (32 to 34 years).Among males, the most frequent malignancies were colorectal carcinoma, lymphoma, leukemia, lung cancer, prostate cancer, urolithial cancer and other cancers (mesothelial, pancreas, stomach and osteosarcoma), respectively. Among females, the most frequent malignancies were breast cancer, thyroid cancer, colorectal carcinoma, lymphoma, leukemia, renal cell carcinoma and other cancers (gall bladder, pancreas, ovary and uterus), respectively.Conclusion: Among males, colorectal carcinoma, lymphoma, leukemia, lung cancer and prostate cancer were the most common cancers. Among females, breast cancer, thyroid cancer, colorectal carcinoma, lymphoma and leukemia were the most common cancers. Our results alarm to initiate the cancer control programs to decrease the cancer incidence in our region.